A Pilot of Brief Mindfulness-Based Intervention to manage emotions in patients with psoriasis - Ramos Díaz, Natalia; Jiménez Jiménez, Óliver; Habicheyn Hiar, Silvia; Roca Alarcón, Ángeles; Rivas Ruiz, Francisco; Resurrección, Davinia; de Troya Martín, Magdalena (Anales de Psicología / Annals of Psychology, 2023)
Psoriasis is a high incidence dermatosis related to stress, and its sufferers provide an appropriate target group to carry out interventions such as those based on mindfulness, aimed at helping emotion regulation. To assess the Compassionate Emotional Accompaniment Technique (CEAT) effects within a brief mindfulness-based intervention on emotional coping in patients with severe psoriasis to determine the efficacy of emotional coping after the induction of a negative emotional state. Forty-four adults (59.1% were women) aged 22-71 years (M = 51.95, SD = 11.87) with severe psoriasis were assigned randomly to the CEAT group or the Emotional Disclosure control group. Subjective discomfort, cognitive ability, affect, and heart rate were assessed before and after the interventions, with two follow-ups at 48 hours and seven days. The results show significant statistical differences in favor of the CEAT intervention versus the Emotional Disclosure group, being more effective in the emotional management after induction and follow-up. These results encourage interventions in a clinical setting with patients with severe psoriasis, so future research should consider using this intervention type to improve emotional management with this population group.